Asuhan Keperawatan pada Pasien Vertigo Menggunakan Terapi Brandt Darrof untuk Mengurangi Tingkat Vertigo - Denti Malasari; Dewi Damayanti; Shanty Chloranyta (Ners Akademika, 2023)
Purpose: Vertigo is a symptom or feeling where it occurs due to a balance disorder, a feeling that feels like floating as if the world is spinning accompanied by nausea and vomiting due to the sensation of spinning that is felt.  Vertigo has 3 levels, there are mild levels, moderate levels and severe levels where the level of signs and symptoms felt can be different for each patient.  Brandt Darrof therapy is a therapy that can improve balance so that it can reduce the level of vertigo because it can improve blood flow to the brain.  The aim of this study was to identify and analyze the effectiveness of Brandt Darrof's therapy in reducing the level of vertigo in vertigo patients in the working area of the Sukabumi Inpatient Public Health Center, Bandar Lampung.  Methodology: This research method uses the applied research method with a quasi-experimental research design.  The subjects of this study used 2 people who met the inclusion criteria including those with a diagnosis of vertigo at the health center, having a history of vertigo for ± 3 months, with a mild vertigo level, communicating well and with patients who were not taking other therapies.  This research instrument used demographic data sheets, Brandt Darrof SOP, vertigo symptom scale – short form (VSS-SF) sheets to measure the level of vertigo in respondents and observation sheets before and after being given Brandt Darrof therapy for 5 days.  Results: The results of the study found that there was a reduction in the level of vertigo in both patients.  Ny. K before being given therapy got a score of 18 (mild vertigo) to a score of 13 (mild vertigo) and Ny. N before being given therapy got a score of 25 (moderate vertigo) to a score of 18 (mild vertigo).  The conclusion of this study is that the application of Brandt Darrof therapy is effectively used in vertigo patients to reduce vertigo levels and improve balance.